Question

\[ \text{Find } 2011^2 - 2010^2 \text{?} \]

Ask by Savage Riley. in South Africa
Feb 16,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The answer is 4021.

Solution

We can use the difference of squares formula: a² - b² = (a + b)(a - b). Here, a = 2011 and b = 2010, so: 2011² - 2010² = (2011 + 2010)(2011 - 2010) = (4021)(1) = 4021. Thus, the answer is 4021.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To find \( 2011^2 - 2010^2 \), we can use the difference of squares formula, which states that \( a^2 - b^2 = (a-b)(a+b) \). In this case, let \( a = 2011 \) and \( b = 2010 \). Calculating the values: \[ a - b = 2011 - 2010 = 1 \] \[ a + b = 2011 + 2010 = 4021 \] Now we can apply the difference of squares formula: \[ 2011^2 - 2010^2 = (2011 - 2010)(2011 + 2010) = 1 \times 4021 = 4021 \] So, \( 2011^2 - 2010^2 = 4021 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy